Adjuvants and rebound pain following peripheral nerve block in adult surgical patients: a systematic review and network meta-analysis of randomized controlled trials - Yang, Xiaodan; Su, Bin; Chen, Yupei; Yang, Jianjun; Huang, He; Chen, Bing (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Purpose Rebound pain occurs when peripheral nerve blocks (PNBs) subside and this hampers patient recovery after surgery. This study aims to determine the most effective adjuvant to mitigate rebound pain in adult surgical patients. Methods A comprehensive search was conducted for randomized controlled trials (RCTs) that reported rebound pain and utilized perineurally (PN) or intravenously (IV) administered adjuvants. We used multiple databases, including PubMed, Web of Science, the Cochrane Library, Embase, CNKI, Wanfang Data, SinoMed and Chinese medical journals from their inception until September 30, 2024. The primary outcome measured was the incidence of rebound pain. A network meta-analysis was performed using a frequentist approach. Results The meta-analysis included three RCTs examining ketamine/esketamine, eight evaluating dexamethasone and one assessing tropisetron. Compared to no adjuvant, IV dexamethasone was found to significantly reduce the incidence of rebound pain (odds ratio [OR] = 0.13, 95% confidence interval [CI]: 0.05, 0.35) and postoperative nausea and vomiting (PONV; OR = 0.33, 95% CI: 0.12, 0.85), while also prolonging the time to onset of rebound pain (mean difference [MD] = 3.95 h, 95% CI: 1.36, 6.53). PN dexamethasone extended the time to onset of rebound pain (MD = 6.57 h, 95% CI: 3.20, 9.93) but did not significantly reduce the incidence of rebound pain or PONV. Ketamine/esketamine was associated with a reduction in the incidence of rebound pain (OR = 0.30, 95% CI: 0.10, 0.89) but did not affect PONV. According to the rank order of surface under the cumulative ranking curve analysis, IV dexamethasone exhibited the lowest incidence of rebound pain and PONV compared to PN dexamethasone, ketamine/esketamine, tropisetron and no adjuvant. PN dexamethasone was most effective in prolonging the onset of rebound pain compared to IV dexamethasone, tropisetron and no adjuvant. The overall quality of evidence was rated as low or very low. Conclusion Current evidence, albeit of low quality, indicates that IV dexamethasone is the most effective adjuvant for the prevention of rebound pain, while PN dexamethasone is optimal for delaying its onset. Therefore, a combined approach utilizing both IV and PN dexamethasone following PNB may represent an effective strategy for managing rebound pain in adult surgical patients.